IMPLEMENTASI REVOLUSI MENTAL DALAM KURIKULUM PENDIDIKAN DASAR - Mumuh Muhtarom (Tatar Pasundan: Jurnal Diklat Keagamaan, 2019)
This article aims to describe the implementation of the mental revolution in basic education. Through analytical descriptive methods, the conclusion is that the mental revolution serves to improve the quality of education and provide solutions to obstacles due to the low quality of education implementers in the field both teachers, schools, supervisors, students, and policymakers in education through the implementation of the curriculum, especially in the basic education. Key words: Character; Personality; Basic education; mental revolution